2000
DOI: 10.1034/j.1399-3011.2000.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent conformation of diethylglycine residues in peptides

Abstract: Diethylglycine (Deg) residues incorporated into peptides can stabilize fully extended (C5) or helical conformations. The conformations of three tetrapeptides Boc-Xxx-Deg-Xxx-Deg-OMe (Xxx=Gly, GD4; Leu, LD4 and Pro, PD4) have been investigated by NMR. In the Gly and Leu peptides, NOE data suggest that the local conformations at the Deg residues are fully extended. Low temperature coefficients for the Deg(2) and Deg(4) NH groups are consistent with their inaccessibility to solvent, in a C5 conformation. NMR evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…In fact, for extended structures small N i H-N iC1 H and large C i aCH-N iC1 H NOEs are to be expected, with C i aCH-N iC1 H NOEs larger than those for C i aCH-N i H, which does not agree with the results reported above 12. …”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In fact, for extended structures small N i H-N iC1 H and large C i aCH-N iC1 H NOEs are to be expected, with C i aCH-N iC1 H NOEs larger than those for C i aCH-N i H, which does not agree with the results reported above 12. …”
contrasting
confidence: 56%
“…[9][10][11] However, it has been also reported that the local sequence may influence the conformation adopted at the disubstituted residue. 12 It is part of our program concerning this class of amino acids to investigate the effect of incorporation of derivatives with side chains larger than methyl into biologically active compounds. Now, we present the synthesis and the results of an investigation by 1 H NMR spectroscopy in connection with molecular mechanics calculations of the conformational behavior of four tetrapeptide analogues of the sequence B23-B26 of insulin having a,a-dialkyl glycine residues at their C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, detailed energy computations and x‐ray diffraction and solution conformational investigations have shown that the picture presented above is not so simple, in that Deg, Dp n g, Db nug, Dvg ( C α,α ‐divinylglycine), Dp r g ( C α,α ‐dipropargylglycine), and Dp c g ( C α,α ‐dicyclopropylglycine) (Figure 1) rich peptides can adopt either the fully extended or the helical conformation depending upon physical state (including solvent polarity) and sequence context, thus emphasizing that energy differences between these two structures, at least at the level of these residues, are small 71–90. The delicate balance between the two conformations has been confirmed by incorporation in a host sequence of a modest point defect [an Abu guest residue perturbing the regular alignment of the side chain of a (Deg) 5 homo peptide], which is enough to drastically bias the preferred conformation toward the 3 10 ‐helix 91.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interestingly, very similar φ, ψ values were also observed for one Aib residue in the linear tetrapeptide Boc-Leu-Aib-Phe-Aib-OMe, which was reported to form a continuous hydrogen-bonded supramolecular helix. 25 The residue Aib 4 adopts a fully extended conformation, so far known to be characteristic of the higher homologs of Aib, like α,α-diethylglycine (Deg), [26][27][28] and α ,α-dipropylglycine (Dpg). 29,30 The torsion angles φ and ψ of the Phe and Aib 6 residues in the Aib 4 - (Tables 2 and 3).…”
Section: Methodsmentioning
confidence: 99%